Alinhamento de tecnologia da informação e estratégia de negócio no âmbito da administração pública federal: o estudo de caso da CNEN - Gomes Junior, Luis Fernando (2013)
After two decades of extensive research and debate, strategic IT alignment, defined as the degree of match between information technology and business strategy remains a top priority for researchers and professionals in information systems and mainly for the Federal Government, which seeks the effective use of IT by their agencies and entities. This study was carried out in an institution of the Federal Government, which owns Strategic Information Technology Plan and Strategic Business Plan, with the purpose of assessing the degree of alignment of IT with the business strategy of the organization. The research method used was the case study and the data collected through a survey instrument called Strategic Alignment Maturity Assessment Tool by Luftman (2003). After the data collection and analysis of the responses, you can identify the level of maturity of the researched entity and demonstrate the points that need to be improved and that deserve greater attention on the part of decisionmakers so that there is the possibility of a successful alignment between the Strategic Information Technology Plan and Strategic Business Plan. The research results contain elements which could serve as a basis for future studies, and to other Federal Government organizations, demonstrating the importance of the relationship between the strategic areas of any organization with IT, in order to optimize the performance and effectiveness desired